A polysaccharide-based hydrogel and its application in food detection

CN116239726BActive Publication Date: 2026-10-27QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211741792.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2026-10-27
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

目前的水凝胶主要存在以下问题:一是天然多糖分子缺乏交联基团,使得以多糖为原料得到的水凝胶易碎;二是作为指示凝胶使用时,其变色范围窄,导致其利用范围窄;三是大多数多糖类水凝胶的透明度较低,使其应用受限

Benefits of technology

[0035]1、本发明提供的多糖基水凝胶,具有多重交联网状结构,提高其对水分的负载能力;经过多重的物理和化学交联,使水凝胶具有柔韧性高的优点;水凝胶组分的多种交联增强了凝胶组分之间的相互作用,提高了水凝胶内部的均匀性,使水凝胶具有透明度高的优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116239726B_ABST
    Figure CN116239726B_ABST
Patent Text Reader

Abstract

The application provides a polysaccharide-based hydrogel and application thereof in food detection, and the polysaccharide-based hydrogel comprises 2-4 parts of carboxylated polysaccharide, 2-4 parts of sodium olefine sulfonate, 0.3-0.6 parts of a high-valence metal salt, 0.055-0.122 parts of a crosslinking agent, 0.034-0.074 parts of an initiator and 10-15 parts of water. The polysaccharide-based hydrogel obtained by compounding the above raw materials by the method has the advantages of good flexibility and good transparency. When the polysaccharide-based hydrogel is prepared into an indicator hydrogel and applied to food detection, the indicator hydrogel can quickly and sensitively detect the gases such as ammonia and hydrogen sulfide produced in food, and has the advantages of fast color developing speed and high detection efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of polymer materials technology and food testing, specifically to a polysaccharide-based hydrogel and its application in food testing. Background Technology

[0002] Hydrogels are novel polymeric materials with a three-dimensional network structure. Polysaccharides are widely available, low-cost, renewable, and biodegradable, making them excellent materials for hydrogel preparation. However, current hydrogels mainly suffer from the following problems: First, natural polysaccharide molecules lack cross-linking groups, making hydrogels obtained from polysaccharides brittle; second, when used as indicator gels, their color change range is narrow, limiting their application; and third, most polysaccharide hydrogels have low transparency, further restricting their applications.

[0003] Meat and seafood are essential foods for obtaining nutrition, and their freshness is closely related to human health. As storage time increases or external environmental changes occur, meat and seafood can spoil, not only damaging their taste and nutritional value but also easily causing various diseases. Therefore, smart packaging that can visually monitor the freshness of meat and seafood is receiving increasing attention.

[0004] The function of freshness indicator materials is to detect changes in the color of the indicator caused by changes in the material's pH, thereby monitoring the decomposition products and microbial metabolites produced by spoilage in food and thus visually displaying the quality of the food. Therefore, the design of the indicator carrier (i.e., the indicator material) is crucial for the sensitive detection of food freshness. Currently, most freshness indicator materials are membrane-based (e.g., Hydroxypropyl Guar / Cellulose Nanocrystal Film with Ionic Liquid and Anthocyanin for Real-Time and Visual Detection of NH3, ACS Sustainable Chemistry & Engineering. 2020, 8, 9731-9741). Although they have a certain degree of hydrophilicity, in low-humidity environments, the lack of an aqueous environment to dissolve spoilage gases reduces the indicator sensitivity of membrane materials.

[0005] Hydrogels, as a three-dimensional network structure material, have a high internal water content, making them a good carrier for food freshness indicators. However, most hydrogels currently available are polysaccharide-based, and their fragility makes them prone to damage and leakage when used as indicators. Furthermore, their low transparency results in low sensitivity when used as color-changing substrates. Additionally, the color-changing range of indicator gels is narrow, only suitable for indicating the freshness of fresh meat (CN114047184A: A method for preparing and applying a smart indicator label for identifying meat freshness) or marine fish (CN114199866A: A color-changing hydrogel microneedle patch, its preparation method, and its application).

[0006] It is evident that providing a hydrogel with good toughness, good transparency, and a wide color change range is of great significance. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a polysaccharide-based hydrogel and its application in food detection. The polysaccharide-based hydrogel comprises carboxylated polysaccharides, sodium olefin sulfonate, high-valent metal salts, crosslinking agents, initiators, and water. The polysaccharide-based hydrogel obtained by combining the above raw materials with the method of this invention exhibits advantages such as good flexibility and high transparency. When prepared as an indicator hydrogel and applied to food detection, it can rapidly and sensitively detect gases such as ammonia and hydrogen sulfide produced in food, offering advantages such as fast color development and high detection efficiency.

[0008] The technical solution of the present invention is as follows:

[0009] A polysaccharide-based hydrogel comprising the following raw materials in parts by weight:

[0010] 2-4 parts carboxylated polysaccharide, 2-4 parts sodium olefin sulfonate, 0.3-0.6 parts high-valence metal salt, 0.055-0.122 parts crosslinking agent, 0.034-0.074 parts initiator, and 10-15 parts water.

[0011] Preferably, the carboxylated polysaccharide is one of carboxymethyl starch, carboxymethyl chitosan, and carboxymethyl dextran.

[0012] Preferably, the sodium olefin sulfonate is one of sodium vinyl sulfonate, sodium allyl sulfonate, and sodium isoallyl sulfonate.

[0013] Preferably, the high-valence metal salt is titanium tetrachloride or germanium tetrachloride.

[0014] Preferably, the crosslinking agent is ethylene glycol dimethacrylate.

[0015] Preferably, the initiator is benzoyl peroxide.

[0016] The above-mentioned polysaccharide-based hydrogel is prepared by the following method:

[0017] (1) Weigh each raw material by weight and set aside for use;

[0018] (2) Place the carboxylated polysaccharide in an Erlenmeyer flask, add water to dissolve it, and then heat and stir it in a water bath at 90±2℃ to obtain a polysaccharide gelatinized solution;

[0019] (3) Cool the polysaccharide gelatinization solution to 50±1℃, add sodium olefin sulfonate to it, and stir for 1-1.5h to obtain a mixed solution of carboxylated polysaccharide / sodium olefin sulfonate.

[0020] (4) Add a high-valence metal salt to a mixed solution of carboxylated polysaccharide / olefin sulfonate and stir for 0.5-1 h to obtain mixture A;

[0021] (5) Add crosslinking agent and initiator to mixture A, stir for 0.5-1h to obtain mixture B;

[0022] (6) Slowly pour the mixture B into a glass plate mold and irradiate it with ultraviolet light for 20-30 minutes to obtain polysaccharide hydrogel.

[0023] Preferably, in step (1), the stirring time is 1-2 hours.

[0024] This invention combines carboxylated polysaccharides, sodium olefin sulfonate, and high-valent metal ions to construct a physically-chemically multi-crosslinked gel network. Physical crosslinking includes hydrogen bonds and metal coordination bonds. The hydroxyl groups on the polysaccharide molecules form abundant hydrogen bonds with the oxygen atoms on the olefin sulfonate, while the carboxyl groups on the carboxylated polysaccharides and the sulfonate groups on the olefin sulfonate together form metal coordination bonds with tetravalent titanium or tetravalent germanium ions. Chemical crosslinking involves the photoinitiated chemical polymerization of the olefin in the sodium olefin sulfonate with the crosslinking agent ethylene glycol dimethacrylate, forming stable chemical bonds. This multi-layered physical and chemical crosslinking improves the flexibility of the hydrogel, providing an excellent carrier for the preparation of indicator gels. Furthermore, the multiple crosslinks of the hydrogel components enhance the interactions between the components, improve the internal uniformity of the hydrogel, and thus increase the transparency of the gel, avoiding the influence of the gel background color on the indicator's color change.

[0025] The above-mentioned polysaccharide-based hydrogel is applied specifically by preparing it into an indicator hydrogel for application.

[0026] Preferably, the indicator hydrogel is prepared as follows:

[0027] (1) Dissolve 0.003 parts of methyl orange, 0.003 parts of methyl red and 0.021 parts of bromothymol blue in 10 parts of 70% ethanol solution and adjust the pH to 7.0±0.1 to obtain an indicator solution;

[0028] (2) Soak the polysaccharide-based hydrogel in the indicator solution for ≥6h to obtain the indicator hydrogel loaded with the indicator.

[0029] The application of the above-mentioned indicator hydrogels in food testing can detect the freshness of food.

[0030] Depending on the requirements, this polysaccharide-based hydrogel can be formulated into indicator hydrogels with different pH color ranges for the detection of different products.

[0031] Preferably, the food is meat products and seafood.

[0032] This invention introduces three indicators into a polysaccharide-based hydrogel: methyl orange (color change pH range 3.1-4.4), methyl red (color change pH range 4.4-6.2), and bromothymol blue (color change pH range 6-7.6), which can cover a wide pH range and indicate the acidic gases produced by meat spoilage and the alkaline gases produced by seafood spoilage.

[0033] In this invention, the hydrogel is characterized by its microstructure, tensile properties, and transparency; the microstructure of the freeze-dried hydrogel is characterized by scanning electron microscopy; the tensile properties of the hydrogel are measured by a digital tensile tester; and the transparency of the hydrogel is determined by taking photographs.

[0034] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0035] 1. The polysaccharide-based hydrogel provided by this invention has a multi-crosslinked network structure, which improves its water loading capacity; through multiple physical and chemical crosslinking, the hydrogel has the advantage of high flexibility; the multiple crosslinking of the hydrogel components enhances the interaction between the gel components, improves the uniformity inside the hydrogel, and gives the hydrogel the advantage of high transparency.

[0036] 2. When the hydrogel provided by this invention is made into an indicator hydrogel for use in food testing, the high flexibility of the hydrogel can avoid mechanical damage and indicator leakage under external force; the high transparency of the hydrogel can avoid interference with the color development of the indicator; by setting the pH range of the indicator, the indicator gel can detect the freshness of food over a wide range.

[0037] 3. The polysaccharide-based hydrogel provided by this invention has the advantages of being safe and non-toxic. When prepared as an indicator hydrogel and applied to food testing, it can quickly and sensitively detect gases such as ammonia and hydrogen sulfide produced in food, and has the advantages of fast color development and high detection efficiency. Attached Figure Description

[0038] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0039] Figure 1 This is a scanning electron microscope image of the polysaccharide-based hydrogel from Example 1.

[0040] Figure 2 The stretch curve is shown for the polysaccharide-based hydrogel of Example 1.

[0041] Figure 3 This is a compression rebound photograph of the polysaccharide-based hydrogel of Example 1.

[0042] Figure 4 This is a transparency characterization diagram of the polysaccharide-based hydrogel in Example 1.

[0043] Figure 5 The colorimetric diagrams are shown for the indicator under different pH conditions in application experiment 1.

[0044] Figure 6 The colorimetric diagrams of the indicator hydrogel from Experiment 1 on different pH buffers are shown.

[0045] Figure 7 To demonstrate the application of the indicator hydrogel from Experiment 1 in indicating the freshness of meat and shrimp.

[0046] Figure 8 This is a scanning electron microscope image of the polysaccharide-based hydrogel from Example 2.

[0047] Figure 9 The stretching curve of the polysaccharide-based hydrogel in Example 2 is shown.

[0048] Figure 10 This is a compression rebound photograph of the polysaccharide-based hydrogel in Example 2.

[0049] Figure 11 This is a transparency characterization diagram of the polysaccharide-based hydrogel in Example 2.

[0050] Figure 12 The colorimetric diagrams of the indicator hydrogel in Experiment 2 on different pH buffers are shown.

[0051] Figure 13 The indicator hydrogel used in Experiment 2 was applied to indicate the freshness of meat and shrimp.

[0052] Figure 14 This is a scanning electron microscope image of the polysaccharide-based hydrogel from Example 3.

[0053] Figure 15The stretch curve of the polysaccharide-based hydrogel in Example 3 is shown.

[0054] Figure 16 This is a compression rebound photograph of the polysaccharide-based hydrogel in Example 3.

[0055] Figure 17 This is a transparency characterization diagram of the polysaccharide-based hydrogel in Example 3.

[0056] Figure 18 The colorimetric diagrams of the indicator hydrogel used in Experiment 3 on different pH buffers are shown.

[0057] Figure 19 The indicator hydrogel from Experiment 3 was used to indicate the freshness of meat and shrimp. Detailed Implementation

[0058] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.

[0059] In the following embodiments of the present invention, carboxymethyl starch, carboxymethyl chitosan, carboxymethyl dextran, sodium vinyl sulfonate, sodium allyl sulfonate, sodium isoallyl sulfonate, titanium tetrachloride, germanium tetrachloride, ethylene glycol dimethacrylate, benzoyl peroxide, methyl red, methyl orange, bromothymol blue, and deionized water are used. All of the above raw materials, glass molds, and ultraviolet lamps were purchased from the market and used directly.

[0060] Example 1

[0061] A polysaccharide-based hydrogel is prepared as follows:

[0062] (1) Weigh 2g of carboxymethyl starch and place it in an Erlenmeyer flask. Add 10g of deionized water to dissolve it. Then heat and stir in a 90℃ water bath for 1.5h to obtain a carboxymethyl starch gelatinized solution.

[0063] (2) Cool the carboxymethyl starch gelatinized solution to 50°C, add 2g of sodium vinyl sulfonate to it, stir for 1h to obtain a mixed solution of carboxymethyl starch / sodium vinyl sulfonate.

[0064] (3) Add 0.3 g of titanium tetrachloride to the carboxymethyl starch / sodium vinyl sulfonate mixed solution and stir for 0.5 h to obtain mixture A;

[0065] (4) Add 0.06g of ethylene glycol dimethacrylate and 0.037g of benzoyl peroxide to mixture A, stir for 0.5h to obtain mixture B;

[0066] (5) Slowly pour the mixture B into a glass plate mold and irradiate it with ultraviolet light for 20 minutes to obtain polysaccharide hydrogel.

[0067] The polysaccharide-based hydrogel prepared in Example 1 was characterized by its microstructure, tensile properties, and transparency, as detailed below:

[0068] Microstructure characterization of polysaccharide-based hydrogels: The polysaccharide-based hydrogels were fractured in liquid nitrogen, then freeze-dried, sputter-coated with gold, and their microstructure was observed using a scanning electron microscope, such as... Figure 1 As shown. From Figure 1 As can be seen, the polysaccharide-based hydrogel is composed of a uniform porous structure at the microscopic level.

[0069] Tensile and compressive properties testing of polysaccharide-based hydrogels: The tensile properties of the polysaccharide-based hydrogels were determined using a tensile tester. The hydrogels were fixed between two clamps, and the tensile rate was set to 100 mm / min. The tensile curves were obtained, as shown in the figure. Figure 2 .from Figure 2 It can be seen that the polysaccharide-based hydrogel has good tensile properties, with an elongation at break of 870%.

[0070] Figure 3 Compression rebound photographs of polysaccharide-based hydrogels, from Figure 3 It is known that polysaccharide-based hydrogels have excellent compression resilience and are not easily damaged in practical applications.

[0071] Transparency analysis of polysaccharide-based hydrogels: A 3 mm thick gel slice was placed on a patterned background, and the transparency was observed. The results are shown below. Figure 4 ;from Figure 4 As can be seen, the pattern behind the polysaccharide-based hydrogel is clearly visible, indicating that the polysaccharide-based hydrogel has excellent transparency.

[0072] Application Experiment 1

[0073] Experiment 1: Analysis of the color development of the indicator solution at different pH values, as detailed below:

[0074] (1) Dissolve 0.003g methyl orange, 0.003g methyl red and 0.021g bromothymol blue in 70% ethanol solution and adjust the pH to 7.0 to obtain indicator solution;

[0075] (2) Add 7.0 mL of buffer solutions with pH values ​​of 2, 4, 6, 7, 8, 9, 10, and 12 to each of the eight small glass vials, and add 2 drops of indicator to each. Shake and observe the color change. Repeat this operation 3-4 times until the buffer solution color changes significantly. See [link to relevant documentation]. Figure 5 .

[0076] like Figure 5 As shown, the indicator exhibits different color development under different pH conditions: orange and red under acidic conditions, and the green color gradually deepens under alkaline conditions.

[0077] Experiment 2: An indicator hydrogel was prepared using the polysaccharide-based hydrogel from Example 1, and a colorimetric experiment was conducted, as detailed below:

[0078] The polysaccharide hydrogel of Example 1 was cut into small pieces and soaked in the indicator solution with pH 7 of Experiment 1 for 6 hours. After soaking, the pieces were placed on a glass plate, and 1 mL of buffer solutions with different pH values ​​from Experiment 1 was dropped onto the gel for color development. The results are shown in [Figure 1]. Figure 6 ;like Figure 6 As shown, the indicator gel loaded with the indicator exhibits different colors depending on the pH.

[0079] Experiment 3: An indicator hydrogel was prepared using the polysaccharide-based hydrogel from Example 1 to indicate the freshness of pork and shrimp, as detailed below:

[0080] Place a piece of pork in a glass bottle and attach the indicator hydrogel (3mm thick) to the inner wall of the glass bottle; place cooked shrimp in a glass bottle and attach the indicator hydrogel to the inner wall of the glass bottle.

[0081] Observe the color change of the indicator hydrogel as the storage time increases, see... Figure 7 ;like Figure 7 As shown, in the beaker containing pork, the gel changed from light green to red over time; in the beaker containing shrimp, the green color of the gel deepened over time, indicating that the polysaccharide-based hydrogel has a good effect on indicating freshness.

[0082] Example 2

[0083] A polysaccharide-based hydrogel is prepared as follows:

[0084] (1) Weigh 3g of carboxymethyl chitosan and place it in an Erlenmeyer flask. Add 12g of deionized water to dissolve it. Then heat and stir in a 90℃ water bath for 1.5h to obtain a carboxymethyl chitosan solution.

[0085] (2) Cool the carboxymethyl chitosan solution to 50°C, add 3g of sodium allyl sulfonate to it, stir for 1h, and obtain a mixed solution of carboxymethyl chitosan / sodium allyl sulfonate.

[0086] (3) Add 0.4 g of titanium tetrachloride to the carboxymethyl chitosan / sodium allyl sulfonate mixed solution and stir for 0.5 h to obtain mixed solution A;

[0087] (4) Add 0.083g of ethylene glycol dimethacrylate and 0.05g of benzoyl peroxide to mixture A, stir for 0.5h to obtain mixture B;

[0088] (5) Slowly pour the mixture B into a glass plate mold and irradiate it with ultraviolet light for 20 minutes to obtain polysaccharide hydrogel.

[0089] The polysaccharide-based hydrogel prepared in Example 2 was characterized by its microstructure, tensile properties, and transparency, as detailed below:

[0090] Microstructure characterization of polysaccharide-based hydrogels: The polysaccharide-based hydrogels were fractured in liquid nitrogen, then freeze-dried, sputter-coated with gold, and their microstructure was observed using a scanning electron microscope, such as... Figure 8 As shown. From Figure 8 As can be seen, the polysaccharide-based hydrogel is composed of a uniform porous structure at the microscopic level.

[0091] Tensile and compressive properties testing of polysaccharide-based hydrogels: The tensile properties of the polysaccharide-based hydrogels were determined using a tensile tester. The hydrogels were fixed between two clamps, and the tensile rate was set to 100 mm / min. The tensile curves were obtained, as shown in the figure. Figure 9 .from Figure 9 It can be seen that the polysaccharide-based hydrogel has good tensile properties, with an elongation at break of 725%.

[0092] Figure 10 Compression rebound photographs of polysaccharide-based hydrogels, from Figure 10 It is known that polysaccharide-based hydrogels have excellent compression resilience and are not easily damaged in practical applications.

[0093] Transparency analysis of polysaccharide-based hydrogels: A 3 mm thick gel slice was placed on a patterned background, and the transparency was observed. The results are shown below. Figure 11 ;from Figure 11 As can be seen, the pattern behind the polysaccharide-based hydrogel is clearly visible, indicating that the polysaccharide-based hydrogel has excellent transparency.

[0094] Application Experiment 2

[0095] Experiment 4: An indicator hydrogel was prepared using the polysaccharide-based hydrogel from Example 2, and a colorimetric experiment was conducted, as detailed below:

[0096] The polysaccharide hydrogel from Example 2 was cut into small pieces and soaked in the indicator solution at pH 7 from Experiment 1 for 6 hours. After soaking, the pieces were placed on a glass plate, and 1 mL of buffer solutions at different pH values ​​from Experiment 1 was dropped onto the gel for color development. The results are shown in [Figure 1]. Figure 12 ;like Figure 12 As shown, the indicator gel loaded with the indicator exhibits different colors depending on the pH.

[0097] Experiment 5: An indicator hydrogel was prepared using the polysaccharide-based hydrogel from Example 2 to indicate the freshness of pork and shrimp, as detailed below:

[0098] Place a piece of pork in a glass bottle and attach a 3mm thick layer of indicator hydrogel to the inner wall of the glass bottle; place cooked shrimp in a glass bottle and attach the indicator hydrogel to the inner wall of the glass bottle.

[0099] Observe the color change of the indicator hydrogel as the storage time increases, see... Figure 13 ;like Figure 13 As shown, in the beaker containing pork, the gel changed from light green to red over time; in the beaker containing shrimp, the green color of the gel deepened over time, indicating that the polysaccharide-based hydrogel has a good effect on indicating freshness.

[0100] Example 3

[0101] A polysaccharide-based hydrogel is prepared as follows:

[0102] (1) Weigh 4g of carboxymethyl dextran and place it in an Erlenmeyer flask. Add 15g of deionized water to dissolve it. Then heat and stir in a 90℃ water bath for 2 hours to obtain a carboxymethyl dextran solution.

[0103] (2) Cool the carboxymethyl dextran solution to 50°C, add 4g of sodium allyl sulfonate to it, stir for 1h, and obtain a mixed solution of carboxymethyl dextran / sodium allyl sulfonate.

[0104] (3) Add 0.4 g of germanium tetrachloride to the carboxymethyl dextran / sodium allyl sulfonate mixed solution and stir for 0.5 h to obtain mixed solution A;

[0105] (4) Add 0.11g of ethylene glycol dimethacrylate and 0.067g of benzoyl peroxide to mixture A, stir for 0.5h to obtain mixture B;

[0106] (5) Slowly pour the mixture B into a glass plate mold and irradiate it with ultraviolet light for 20 minutes to obtain polysaccharide hydrogel.

[0107] The polysaccharide-based hydrogel prepared in Example 3 was characterized by its microstructure, tensile properties, and transparency, as detailed below:

[0108] Microstructure characterization of polysaccharide-based hydrogels: The polysaccharide-based hydrogels were fractured in liquid nitrogen, then freeze-dried, sputter-coated with gold, and their microstructure was observed using a scanning electron microscope, such as... Figure 14 As shown. From Figure 14 As can be seen, the polysaccharide-based hydrogel is composed of a uniform porous structure at the microscopic level.

[0109] Tensile and compressive properties testing of polysaccharide-based hydrogels: The tensile properties of the polysaccharide-based hydrogels were determined using a tensile tester. The hydrogels were fixed between two clamps, and the tensile rate was set to 100 mm / min. The tensile curves were obtained, as shown in the figure. Figure 15 .from Figure 15 It can be seen that the polysaccharide-based hydrogel has good tensile properties, with an elongation at break of 868%.

[0110] Figure 16 Compression rebound photographs of polysaccharide-based hydrogels, from Figure 16 It is known that polysaccharide-based hydrogels have excellent compression resilience and are not easily damaged in practical applications.

[0111] Transparency analysis of polysaccharide-based hydrogels: A 3 mm thick gel slice was placed on a patterned background, and the transparency was observed. The results are shown below. Figure 17 ;from Figure 17 As can be seen, the pattern behind the polysaccharide-based hydrogel is clearly visible, indicating that the polysaccharide-based hydrogel has excellent transparency.

[0112] Application Experiment 3

[0113] Experiment 6: An indicator hydrogel was prepared using the polysaccharide-based hydrogel from Example 3, and a colorimetric experiment was conducted, as detailed below:

[0114] The polysaccharide hydrogel of Example 3 was cut into small pieces and soaked in the indicator solution with pH 7 of Experiment 1 for 6 hours. After soaking, the pieces were placed on a glass plate, and 1 mL of buffer solutions with different pH values ​​from Experiment 1 was dropped onto the gel for color development. The results are shown in [Figure 1]. Figure 18 ;like Figure 18 As shown, the indicator gel loaded with the indicator exhibits different colors depending on the pH.

[0115] Experiment 7: An indicator hydrogel was prepared using the polysaccharide-based hydrogel from Example 3 to indicate the freshness of pork and shrimp, as detailed below:

[0116] Place a piece of pork in a glass bottle and attach a 3mm thick layer of indicator hydrogel to the inner wall of the glass bottle; place cooked shrimp in a glass bottle and attach the indicator hydrogel to the inner wall of the glass bottle.

[0117] Observe the color change of the indicator hydrogel as the storage time increases, see... Figure 19 ;like Figure 19 As shown, in the beaker containing pork, the gel changed from light green to red over time; in the beaker containing shrimp, the green color of the gel deepened over time, indicating that the polysaccharide-based hydrogel has a good effect on indicating freshness.

[0118] Based on the above embodiments and application test results, it can be seen that the polysaccharide-based hydrogel provided by the present invention has high consistency in three repeated experiments, and the obtained polysaccharide-based hydrogel has the advantages of good flexibility, high elongation at break and good color-changing indication effect.

[0119] Although the present invention has been described in detail with reference to preferred embodiments, it is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be determined by the scope of the claims.

Claims

1. A polysaccharide-based hydrogel, characterized in that, The raw materials include the following parts by weight: 2-4 parts carboxylated polysaccharide, 2-4 parts sodium olefin sulfonate, 0.3-0.6 parts high-valent metal salt, 0.055-0.122 parts crosslinking agent, 0.034-0.074 parts initiator, and 10-15 parts water; The high-valence metal salt is titanium tetrachloride or germanium tetrachloride; The carboxylated polysaccharide is one of carboxymethyl starch, carboxymethyl chitosan, and carboxymethyl dextran; The sodium olefin sulfonate is one of sodium vinyl sulfonate, sodium allyl sulfonate, and sodium isoallyl sulfonate; The crosslinking agent is ethylene glycol dimethacrylate; the initiator is benzoyl peroxide; The preparation method of this polysaccharide-based hydrogel is as follows: (1) Weigh each raw material according to weight and set aside for use; (2) Place the carboxylated polysaccharide in an Erlenmeyer flask, add water to dissolve it, and then heat and stir in a water bath at 90±2℃ for 1-2 hours to obtain a polysaccharide gelatinized solution; (3) Cool the polysaccharide gelatinization solution to 50±1℃, add sodium olefin sulfonate to it, and stir for 1-1.5h to obtain a mixed solution of carboxylated polysaccharide / sodium olefin sulfonate; (4) Add a high-valence metal salt to a mixed solution of carboxylated polysaccharide / olefin sulfonate and stir for 0.5-1 h to obtain mixture A; (5) Add crosslinking agent and initiator to mixture A, stir for 0.5-1h to obtain mixture B; (6) Slowly pour mixture B into a glass plate mold and irradiate with ultraviolet light for 20-30 minutes to obtain polysaccharide-based hydrogel; Carboxylated polysaccharides, sodium olefin sulfonate, and high-valence metal ions were used to construct a physicochemically cross-linked gel network. Physical crosslinking includes hydrogen bonds and metal coordination bonds. In this process, the hydroxyl groups on the polysaccharide molecule form abundant hydrogen bonds with the oxygen atoms on the olefin sulfonic acid, and the carboxyl groups on the carboxylated polysaccharide and the sulfonate groups on the olefin sulfonic acid together form metal coordination bonds with tetravalent titanium ions or tetravalent germanium ions. Chemical crosslinking is the chemical polymerization of the olefin of sodium olefin sulfonate and the crosslinking agent ethylene glycol dimethacrylate under photoinitiation to form stable chemical bonds.

2. The application of the polysaccharide-based hydrogel according to claim 1, characterized in that, Specifically, the polysaccharide-based hydrogel is prepared into an indicator hydrogel for application.

3. The application as described in claim 2, characterized in that, The indicator hydrogel is prepared as follows: (1) Dissolve 0.003 parts of methyl orange, 0.003 parts of methyl red and 0.021 parts of bromothymol blue in 10 parts of 70% ethanol solution and adjust the pH to 7.0±0.1 to obtain an indicator solution; (2) Soak the polysaccharide-based hydrogel in the indicator solution for ≥6h to obtain the indicator hydrogel loaded with indicator.

4. The application as described in claim 3, characterized in that, The application of indicator hydrogels in food testing.

5. The application as described in claim 4, characterized in that, The food products mentioned are meat products and seafood products.

Citation Information

Patent Citations

  • Preparation method and application of intelligent indication label for identifying freshness of meat products

    CN114047184A

  • Dual-network hydrogel bionic intelligent skin and preparation method thereof

    CN113427876A

  • Color-changeable hydrogel microneedle patch as well as preparation method and application thereof

    CN114199866A